2012
DOI: 10.1002/cae.20383
|View full text |Cite
|
Sign up to set email alerts
|

A virtual platform to teach separation processes

Abstract: In this article the Unit Operations and Separation Processes area of a virtual platform called LABVIRTUAL (http://labvirtual.eq.uc.pt) is presented aiming to support the autonomous study of undergraduate students engaged in a Chemical Engineering degree, especially in Portuguese-speaking countries. The main features, subjects, computational applications, and examples in the platform are described, as well as a first assessment by the students. ß

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 8 publications
0
16
0
Order By: Relevance
“…Interesting works have been reported on the description of teaching methodologies in the topic of unit operations and separation processes that complement the autonomous study of a diversity of topics in chemical thermodynamics, transfer phenomena and process separation [1], simulation and optimization of a crude distillation unit [2], description of software explaining process, simulators to undergraduate students in unit operation courses and comprising the simulation of chemical processes [3]. Accordingly, the use of educational software has gained more attention because it helps during the teaching process by providing an alternative and complement approach to the analysis of information.…”
Section: Introductionmentioning
confidence: 99%
“…Interesting works have been reported on the description of teaching methodologies in the topic of unit operations and separation processes that complement the autonomous study of a diversity of topics in chemical thermodynamics, transfer phenomena and process separation [1], simulation and optimization of a crude distillation unit [2], description of software explaining process, simulators to undergraduate students in unit operation courses and comprising the simulation of chemical processes [3]. Accordingly, the use of educational software has gained more attention because it helps during the teaching process by providing an alternative and complement approach to the analysis of information.…”
Section: Introductionmentioning
confidence: 99%
“…These are classic operations in chemical industries since, frequently, the preparation of raw materials or the separation of products, either before or after the reactions, require a combination of them. A detailed description of the contents, simulators, as well as case studies in this topic can be found in a previous work . The Chemical Reaction's section covers many aspects of the chemical reaction science, the modeling and design of reactors for both homogeneous and heterogeneous catalysis.…”
Section: Description Of Labvirtualmentioning
confidence: 99%
“…Process simulations have been successfully integrated into chemical engineering textbooks . Regarding the articles, the use of commercial and noncommercial process simulators with educational purpose has also been extensively reported . However, the details on how to use the simulator's capabilities for improving the students’ understanding are not always provided.…”
Section: Introductionmentioning
confidence: 99%